CARBONATE BIOFACIES AND PALEOECOLOGY ANALYSIS BASED ON ACROPORA CORAL IN UJUNGGENTENG AREA, WEST JAVA PROVINCE, INDONESIA - Wahyu Dwijo Santoso (Indonesian Institute of Sciences, 2017)
Biofacies concept was proposed to approach the carbonate facies determination by using coral species description and ecology reconstruction. Ujunggenteng area was selected for this study because it has modern carbonate rocks with continues distribution and contains many well-preserved coral fossils. Ujunggenteng area can be distinguished into three biofacies: Acropora cervicornis – Acropora palifera biofacies, Acropora gemmifera – Acropora humilis biofacies, and Acropora cervicornis – Acropora palmata biofacies. The paleobathymetry analysis had indicated that Acropora cervicornis – Acropora palifera biofacies grew in the deepest environment, between 8 – 13 meters depth. Acropora gemmifera – Acropora humilis biofacies lived in a shallower environment between 3 – 8 meters depth, and Acropora cervicornis – Acropora palmata biofacies was deposited between 0 – 3 meters. The Mg/Ca trend showed a negative correlation with the paleobathymetry result. Decreasing Mg/Ca ratio was related to increasing paleobathymetry. Acropora cervicornis – Acropora palifera biofacies has the smallest Mg/Ca ratio, between 14 – 15 mmol. Acropora gemmifera – Acropora humilis biofacies has Mg/Ca ratio between 17 – 21 mmol. Acropora cervicornis – Acropora palmata biofacies has the highest Mg/Ca ratio, between 23 – 24 mmol. Mg/Ca ratio value was related to paleotemperature, in which the decreasing of Mg/Ca ratio associated to decreasing paleotemperature.Konsep biofasies dipilih dan diajukan sebagai salah satu pendekatan untuk penentuan fasies karbonat. Daerah Ujunggenteng dipilih untuk studi ini karena daerah ini menunjukkan perkembangan batuan karbonat yang menerus dan fosil koral yang terawetkan dengan baik. Daerah Ujunggenteng dapat dibagi menjadi tiga biofasies, yaitu biofasies Acropora cervicornis – Acropora palifera, biofasies Acropora gemmifera – Acropora humilis biofacies, dan biofasies Acropora cervicornis – Acropora palmata. Analisis paleobatimetri menunjukkan bahwa biofasies Acropora cervicornis – Acropora palifera tumbuh di lingkungan yang paling dalam, yaitu 8 – 13 meter. Biofasies Acropora gemmifera – Acropora humilis hidup di lingkungan yang lebih dangkal, yaitu 3 – 8 meter, dan biofasies Acropora cervicornis – Acropora palmata terendapkan di lingkungan yang lebih dangkal, yaitu 0 – 3 meter. Analisis kadar Mg/Ca menunjukkan nilai yang berlawanan dengan paleobatimetri. Penurunan kadar Mg/Ca memiliki hubungan dengan peningkatan paleobatimetri. Biofasies Acropora cervicornis – Acropora palifera memiliki nilai kadar Mg/Ca paling rendah, yaitu 14 – 15 mmol. Biofasies Acropora gemmifera – Acropora humilis memiliki kadar Mg/Ca yang lebih tinggi dibandingkan dengan biofasies Acropora cervicornis – Acropora palifera, yaitu 17 – 21 mmol. Biofasies Acropora cervicornis – Acropora palmata menunjukkan nilai kadar Mg/Ca yang paling tinggi, yaitu 23 – 24 mmol. Kadar Mg/Ca memiliki hubungan dengan perubahan paleotemperatur. Penurunan kadar Mg/Ca berasosiasi dengan penurunan paleotemperatur.